The effects of season and microhabitat on the distribution and nutritional contributions of two algal symbionts in the intertidal anemone Anthopleura xanthogrammica - Levine, Michael Rory (Western Washington University, 2010)
The intertidal sea anemone Anthopleura xanthogrammica is distributed widely along the Pacific coast, from Baja California Mexico (~30ºN) to southern Alaska (57ºN). In much of its range, A. xanthogrammica has the ability to co-host algal symbionts from two distinct taxa known as zoochlorellae (the chlorophyte Elliptochloris marina) and zooxanthellae (brown dinophytes in the genus Symbiodinium). Laboratory studies and field distributions have demonstrated that zoochlorellae and zooxanthellae represent "cool" and "warm" symbionts respectively, based on their relative temperature tolerances and intertidal distributions. This study examined the effects of two intertidal microhabitats on the seasonal distribution, density, and mitotic index of zoochlorellae and zooxanthellae in tentacles of A. xanthogrammica at Slip Point, Clallam Bay WA (48ºN). Tentacles were sampled from anemones at both the lower and upper intertidal limits of the distribution of A. xanthogrammica in tidepools and surge channels in July 2008, November 2008, and April 2009. Temperatures in these microhabitats were recorded with data loggers from summer 2008 to summer 2009. The surge channel microhabitat at Slip Point experienced more extreme temperatures (both higher high temperatures and lower low temperatures) than the tidepool. The distribution and density of zoochlorellae (but not of zooxanthellae) in A. xanthogrammica tentacles differed in these microhabitats. Anemone tentacles containing dense zoochlorellae assemblages predominated in low intertidal tidepools and low surge channels as well as in the high tidepool microhabitat; zoochlorellae density was much lower in the high surge channel. The density of zooxanthellae was low in all microhabitats, and was often nearly one order of magnitude lower than that of zoochlorellae. Patterns in symbiont density in anemones between microhabitats were consistent in all seasons. Comparatively high temperatures in the high surge channel are the likely cause of the reduced density of zoochlorellae (and of the higher proportion of zooxanthellae) in this microhabitat. The distribution of zoochlorellae was not related to differences in algal growth rates alone, as there were no significant differences in the mitotic index of zoochlorellae from the high tidepool and the high surge channel algal populations, despite large differences in algal density of tentacles between these two habitats. Symbiont composition was stable seasonally, with more than 80% of anemone tentacles containing predominantly zoochlorellae in all seasons. The relative contributions of zoochlorellae, mixed algal assemblages composed primarily of zoochlorellae, and of Mytilus californianus mussels (the dominant heterotrophic food source) to the diet of A. xanthogrammica were estimated using stable isotope analysis in summer 2008 and spring 2009. The carbon contributions of symbionts (~62-70%) were greater than those of external food sources (~31-38%) in both seasons. Zoochlorellae contribute substantially to A. xanthogrammica diet, based on analysis of tentacle samples. A. xanthogrammica is proposed as an ideal model intertidal organism for following long-term biological responses to climate change. Because it is long lived and may host both "cool" and "warm" symbionts that are stable in response to seasonal temperature patterns, shifts in symbiont populations (monitored using non-lethal sampling of tentacles) in high intertidal anemones may be used to indicate long-term biological responses to changing thermal conditions.